UKRAINE’S HIGHER EDUCATION AND THE BOLOGNA PROCESS - Abbas, Najam (Збірник наукових праць Військового інституту Київського національного університету імені Тараса Шевченка, 2016)
The article deals with the present condition of Ukraine’s higher education system. Ukraine’s higher education system has a significant potential for more productively utilising the possibility of utilising its strong educational foundations so that its universities can compete with universities elsewhere. Ukraine has great possibilities for increasing its competitiveness and meeting the essential prerequisites to develop universities which are globally competitive.